POINTWISE MULTIPLIERS ON INHOMOGENEOUS BESOV AND TRIEBEL-LIZORKIN SPACES IN THE SETTING OF SPACES OF HOMOGENEOUS TYPE - Han, Yanchang (Taiwanese journal of mathematics, 2013)
Using the discrete Calderón reproducing formula in [9] and the Plancherel-Pôlya characterization of the inhomogeneous Besov and Triebel-Lizorkin spaces developed in [5], we prove pointwise multipliers on inhomogeneous Besov and Triebel-Lizorkin spaces in the setting of spaces of homogeneous type. 2010Mathematics Subject Classification: Primary 46E35; Secondary 42B25, 42B35. Key words and phrases: Pointwise multiplier, Multiplication operator, Besov and Triebel-Lizorkin space, Calderón reproducing formula, Space of homogeneous type.